A statistical method to model non-stationarity in precipitation records changes - Gonzalez, Paula; Naveau, Philippe; Thao, Soulivanh; Worms, Julien (HAL CCSD, 2023)
International audience In the context of climate change, assessing how likely a particular change or event has been caused by human influence is important for mitigation and adaptation policies. In this work we propose an extreme event attribution (EEA) methodology to analyze yearly maxima records, key indicators of climate change that spark media attention and research in the EEA community. Although they deserve a specific statistical treatment, algorithms tailored to record analysis are lacking. This is particularly true in a non-stationarity context. This work aims at filling this methodological gap by focusing on records in transient climate simulations. We apply our methodology to study records of yearly maxima of daily precipitation issued from numerical climate model IPSL-CM6A-LR. Illustrating our approach with decadal records, we detect in 2023 a clear human induced signal in half of the globe, with probability mostly increasing, but decreasing in the south and north Atlantic oceans